Making and Validating a Promotive and Preventive Effort Model for Stages 1-5 of Chronic Kidney Disease in Primary Care Services - Anita Rahman Hajam; Bambang Djarwoto; Mora Claramita (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2022)
Background: The prevalence of Chronic Kidney Disease (CKD) is continuously increasing worldwide, including in Indonesia and has become a global public health problem. With the increased number of patients with CKD and the limited number of nephrologists, primary care physicians and specialists should play an important role in providing quality sustainable prevention and treatment by improving promotive and preventive efforts in primary care. Most patients with CKD can be managed by doctors in primary care in collaboration with specialist doctors in secondary and tertiary care. However, clinical practice guidelines for promoting and preventing CKD in primary care apparently have not been optimally implemented.Objective: This research aimed to make a promotive and preventive model for stages 1-5 of CKD in primary care.Methods: This research employed a research and development strategy with the following stages: (1) Preliminary study stage (literature review), (2) Development stage (initial draft of the model) and (3) Resources validation stage (in-depth interviews).Results: Five primary care physicians, two internists and one nephrologist participated in the validation stage for the initial draft of the model. The three stages of this research obtained the pattern of doctor's practice for CKD and the feedback related to the model to be adjusted according to the condition of primary care in Indonesia.Conclusion: There is a lack of understanding and awareness of primary care physicians about prevention and treatment of CKD, and a lack of supporting examination facilities for serum creatinine and albuminuria in primary care for screening of the risk factors of CKD. A promotional and preventative model of stages 1-5 for CKD in primary care was successfully made and validated.